BEHIND THE OFFERINGS AND PRAYERS: UNCOVERING SYNCRETISM IN THE PRESENTATION OF OFFERINGS IN CATAK HAMLET, KEBONAGUNG VILLAGE - Melya Milviana; Farikhatul Maulidah; Umi Nur Habibah; Pasya Nurul Ramadhani; Khaulah Rizka Awwaliya (PT. Jurnal Center Indonesia Publisher, 2026)
This research examines the manifestation of syncretism in Dusun Catak, Kebonagung Village, Sumowono District, Semarang Regency, with a focus on the tradition of offering sesajen and its interaction with Islamic teachings. The aims of this research are to understand how syncretism is manifested in the lives of the Dusun Catak community, to comprehend the history of Dusun Catak, and to analyze the Islamic perspective on the practice of offering sesajen carried out by the Dusun Catak community. This research uses a descriptive qualitative method, combining literature study by exploring previous research, conducting direct observations at the research location for four days, and performing in-depth interviews with several informants. The results show that syncretism in Dusun Catak is manifested in a unique form, where the tradition of sesajen adapts to Islamic teachings. The Dusun Catak community also preserves the village's historical traditions by passing them down through generations. The placement of sesajen is carried out in specific locations. The practice of offering sesajen is regarded as a form of local wisdom that is not perceived as deviating from religious norms by the community; although the offerings are placed in various locations and are associated with respect for the ancestors of the Catak community, the practice is understood as part of a cultural tradition that is integrated with the Islamic values upheld by the community.